Hyperactivity in male and female mice manifests differently following early, acute prenatal alcohol exposure and mild juvenile stress - Pietrantonio, Amy F.; Urian, Raluca A.; Hardy, Daniel B.; Allman, Brian L.; Willmore, Katherine E. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionChronic prenatal alcohol exposure (PAE) and severe juvenile stress independently contribute to hyperactive and depressive behavioral phenotypes, with their combination exacerbating these effects. However, while chronic PAE and traumatic juvenile stress are well-studied, little is known about the impact of early, acute PAE and mild juvenile stress on hyperactivity and depression. This knowledge gap is clinically relevant, as these milder early-life insults are common in Western societies. Here, we provide the first investigation into the effects of early, acute PAE and juvenile sub-chronic, unpredictable, mild stress (SUMS)—both independently and in combination—on hyperactivity and depressive-like behaviors in mice throughout the lifespan.MethodsWe assessed hyperactivity through movement-related measures (i.e., distance traveled, thigmotaxis, and rearing), whereas depressive-like behaviors were evaluated using the u-shaped two-choice field and forced swim tests. Behavioural testing was performed on equivalent numbers of male and female offspring and repeated at juvenile, adolescent, and adult timepoints to enable assessment of sex and age effects.ResultsNeither early, acute PAE, juvenile SUMS, nor their combination induced depressive-like behaviors at any age; findings in contrast to the more severe chronic PAE and stress insults used in previous studies. However, these milder early-life insults did result in various hyperactivity phenotypes in both the male and female offspring. For example, juvenile SUMS had the strongest impact on hyperactive behaviors across both sexes, but only the adolescent females exhibited increased emotionality-associated activity. Moreover, early, acute PAE—both alone and in combination with juvenile SUMS significantly increased movement during adolescence and adulthood exclusively in male offspring.DiscussionThus, our collective findings not only indicate that early, acute PAE and juvenile SUMS influence hyperactivity in a sex- and age-dependent manner, but also highlight that their influence on hyperactive and depressive phenotypes do not simply mirror those of the more severe early-life insults. Given the potential prevalence of early, acute alcohol exposure and juvenile stress in Western society, further research is warranted to fully understand their long-term behavioral consequences.